Sposoby wspierania zarządzania w małych i średnich przedsiębiorstwach w świetle badań własnych - Nowosielski, Stanisław; Marciszewska, Anna (The means of supporting management in small and medium enterprises in the light of own research, 2006)
The article describes the means’ typology of supporting management in small and medium enterprises. It presents the units reinforcing managing processes. The results of an enquiry in this matter are shown. The author makes an attempt of overall (systemic) introduction of management support issues in small and medium enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 284-293